Video-based assistive aid for blind people using object recognition in dissimilar frames. (9th October 2019) - Jabnoun, Hanen; Benzarti, Faouzi; Morain-Nicolier, Frédéric; Amiri, Hamid
Developing visual aids for handicapped persons is an active research area in the computer vision community. This paper presents a visual substitution tool for blind people based on object recognition in video scene. It focuses on the optimisation of the video processing using the calculation of dissimilarity between frames. The approach includes the real valued local dissimilarity map method in the frames dissimilarity measures. It uses scale invariant features transform keypoints extraction and matching to identify objects in dissimilar frames. The experiment tests showsome encouraging results in the case of finding object of interest. Thus, the proposed method can be a choice for solving the problem of blind and disabilities persons in their interaction with the surrounding environment.